The Role of Human Rights Watch in Reducing Child Labor in Indonesia's Tobacco Fields (2014-2017) - Tika Sabrina (Universitas Muhammadiyah Malang, 2022)
This research discusses about one of the roles of NGOs (Non-Governmental Organizations) in overcoming the issue of child labor in tobacco fields in Indonesia. This type of research is descriptive with a research question, namely